KARAKTERISTIK IBU BERSALIN DENGAN PREEKLAMPSIA DI RSUD SARAS HUSADA PURWOREJO - Wilis Sukmaningtyas; Marfuatus Solikhah (Universitas Harapan Bangsa Purwokerto, 2011)
Background: One of the causes of the high maternal mortality rate ispreeclampsia-eclampsia were ranked second after the bleeding with a percentageof 25% of all causes of maternal mortality. The incidence of preeclampsia inSaras Husada Hospital Purworejo continues to increase every year. In 2009 atotal of 90 cases (4.01%) of the 2,243 deliveries and increased in 2010 to 142cases (6.23%) of the 2,280 deliveries. Objective: To determine the characteristics of the birth mothers withpreeclampsia in Saras Husada Hospital Purworejo 2009-2010. Methods: This research method is quantitative descriptive retrospectiveapproach. The population in this study were all women giving birth with 232maternal preeclampsia, the sampling technique total sampling amounted to 232maternal. This study uses secondary data extracted from medical records spaceSaras Husada Hospital Purworejo. Instrument in this study using the mastertable. Results: The incidence of preeclampsia 2009-2010yaitu period 5.13%.Based on the classification of preeclampsia, the majority of women suffer fromsevere preeclampsia at 76.72%. Characteristics of maternal preeclampsia basedon the age of majority in the age group 20-35 years who suffered severepreeclampsia majority of 59.05%, based largely on the parity parity groups 2-5(multiparous) that a majority of 43.10% experienced severe preeclampsia andpreeclampsia 14.66% lighter. Conclusion: Characteristics of maternal preeclampsia based on the age ofmajority at the age of 20-35 years is 75.86%, based on the parity mostly occurs in2-5 parity (multiparous) is 57.76%. Keywords: maternal characteristics, preeclampsia.